ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR SUZUKI DI KOTA SEMARANG - Septyawan, Bagus Yudo; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2017)
This research is motivated by motorcycle sales, which more and more, that there is in the city of Semarang with many popping latest motorcycle that declined in 2015. Suzuki Motorcycle Sales decreased in 2015. In addition Motorcycles Suzuki has competitors like brand Yamaha, Honda, and Kawasaki. The purpose of this study was to determine the effect of price perception, Quality Products and Quality Service to Purchase Decision Suzuki Motorcycles in Semarang City.In this study were collected through a questionnaire distributed in the city of Semarang obtained by the method of non-probability samples and purposive sampling. Analysis of data obtained both qualitatively and quantitatively. Mechanical test data used in this study include testing instrument (Validity, reliability test, test heterokedastisitas), regression analysis, Test Goodness of fit, coefficient of determination (R2), Feasibility Model (Test F), Test of Effect Causality (t test). Data - data that has met the validity, reliability, and classical assumption processed with SPSS for Windows 20, resulting in a regression equation as follows:Y = 0.240 X1 + 0.589 X2 + 0.376 X3Where hypothesis testing using t test shows that the third independent variable is the price (X1), product quality (X2), and quality of service (X3) significant positive effect on the purchase decision (Y).